Correlating dermatoscopic features with immunohistochemical markers in basal cell carcinoma: a comprehensive analysis of 100 cases in Caucasian population - Calik, Jacek; Sauer, Natalia; Giedziun, Piotr; Piotrowska, Aleksandra; Tumiłowicz, Maciej; Wojnar, Andrzej; Dzięgiel, Piotr (Frontiers in Oncology, 2024)
BackgroundBasal Cell Carcinoma (BCC) is the most common form of skin cancer, characterized by its low metastatic potential yet considerable diversity in clinical and dermatoscopic presentation. Advances in dermatoscopy have significantly improved the early detection of BCC, revealing specific patterns that guide diagnosis and management. Parallelly, immunohistochemical markers have been explored for their potential to elucidate the underlying tumor biology and prognosis, with particular focus on angiogenesis, melanocytic activity, and lymphangiogenesis.ObjectiveThis study aims to investigate the correlations between dermatoscopic features and the immunohistochemical expressions of CD34, CD31, Melan-A, and D2-40 in BCC, through a comprehensive analysis of 100 cases We sought to determine whether visual dermatoscopic patterns correlate with the molecular characteristics defined by immunohistochemical staining, potentially enhancing diagnostic accuracy.MethodsA total of 100 cases of clinically and histopathologically confirmed BCC were prospectively analyzed, employing standard dermatoscopic techniques for lesion evaluation and immunohistochemical staining for CD34, CD31, Melan-A, and D2-40 to assess tumor angiogenic potential, melanocytic activity, and lymphangiogenesis. The study was conducted with adherence to ethical standards and informed consent from all participants.ResultsDermatoscopic examination revealed a variety of vascular patterns and pigmented features across different BCC anatomical locations. However, the comprehensive correlation analysis predominantly found a lack of significant associations between dermatoscopic appearances and expressions of the targeted immunohistochemical markers, with the notable exception of a correlation between observed hemorrhage and the Melan-A marker.ConclusionsThe lack of significant correlations between dermatoscopic features and immunohistochemical marker expressions in BCC suggests that the biological behavior and angiogenic, melanocytic, and lymphangiogenic activities within BCC lesions may be influenced by factors beyond those assessed in this study. Despite the exploratory nature of these findings, they underscore the complexity of BCC biology and highlight the need for further research incorporating additional markers and advanced imaging techniques.